Neurobehavioral outcomes in young adults with perinatally acquired HIV. (15th November 2020) - Coutifaris, Paulina; Byrd, Desiree; Childs, Jocelyn; Clark, Uraina; Posada, Roberto; Robbins, Reuben; Morgello, Susan
Abstract : Background: With combination antiretroviral therapy (cART), infants with perinatally acquired HIV (pHIV) are living into adolescence and adulthood. Worldwide, many have not received cART in the first years of life, and challenges of adolescence complicate transition to adulthood. Neurobehavioral outcomes in pHIV young adults (pHIVAd) are infrequently reported. Objectives: To examine neurobehavioral characteristics of pHIVAd ages 21—30 years, and to compare them with age-matched young adults infected in the second or third decade of life (HIVagematch), and older adults with similar duration HIV disease (HIVOA). Methods: A comprehensive neuropsychological test battery and questionnaires to determine cognitive function and mood, and reviews of neuromedical and behavioral records were undertaken in three groups of 13 individuals each. Descriptive analysis and bivariate techniques were used for comparisons. Results: Rates of cognitive impairment were highest in pHIVAd (85%) compared with HIVagematch (38%) and HIVOA (62%). pHIVAd had the worst scores in global cognition, speed of information processing, working memory, and verbal fluency (0.5–1.0 SD below other groups). There was a trend for higher rates of psychiatric dysfunction (predominantly mood disorders) in pHIVAd (85%) compared with HIV-agematch (46%) and HIVOA (54%). Only four pHIVAd reported employment or enrollment in school. Four had autoimmune disorders. Conclusion: These pHIVAd displayed high rates of cognitive, psychiatric, and autoimmune dysfunction, greater than age-matched or HIV duration-matched comparators. Although this small study is largely descriptive in nature, it suggests that a lack of cART in early life may result in long-term neurobehavioral and immune abnormalities manifesting into adulthood. Abstract : Supplemental Digital Content is available in the text